Moral Distress and Attitudes About Timing Related to Comfort Care for Hospitalized Patients: A Survey of Inpatient Providers and Nurses. (November 2019) - Bender, Melissa A.; Andrilla, C. Holly A.; Sharma, Rashmi K.; Hurd, Caroline; Solvang, Nicole; Mae-Baldwin, Laura
Context: Providing nonbeneficial care at the end of life and delays in initiating comfort care have been associated with provider and nurse moral distress. Objective: Evaluate provider and nurse moral distress when using a comfort care order set and attitudes about timing of initiating comfort care for hospitalized patients. Methods: Cross-sectional survey of providers (physicians, nurse practitioners, and physician assistants) and nurses at 2 large academic hospitals in 2015. Providers and nurses were surveyed about their experiences providing comfort care in an inpatient setting. Results: Two hundred five nurse and 124 provider surveys were analyzed. A greater proportion of nurses compared to providers reported experiencing moral distress "some, most, or all of the time" when using the comfort care order set (40.5% and 19.4%, respectively, P = .002). Over 60% of nurses and providers reported comfort care was generally started too late in a patient's course, with physician trainees (81.4%), as well as providers (80.9%) and nurses (84.0%) < 5 years from graduating professional school most likely to report that comfort care is generally started too late. Conclusions: The majority of providers and nurses reported that comfort care was started too late in a patient's course. Nurses experienced higher levels of moral distress than providers when caring for patients using a comfort care order set. Further research is needed to determine what is driving this moral distress in order to tailor interventions for nurses and providers.